Penurunan Kadar Ammonia dan Phospat pada Limbah Cair dengan Menggunakan Tanaman Enceng Gondok di RSUD Dr. Pirngadi Medan - sukati sukati; Meida Nugrahalia; Abdul Karim (Universitas Medan Area, 2021)
The purpose of this study was to reduce the levels of ammonia (NH3) and phosphate (PO4) in water hyacinth (Eichornia crassipes) experimentally with contact times with water hyacinth 24 hours, 48 hours and 72 hours. Water hyacinth has 2 plants, 4 plants, 6 plants and 1 control bucket. From the results of this study, the contact time of 24 hours can reduce ammonia levels by 46% - 82% and phosphate content by 33% - 56%. The ammonia content can be reduced by 71% - 87%, the phosphate content by 58% - 90% with a contact time of 48 hours, and the ammonia content can be reduced by 89% - 91% with a contact time of 72 hours. . Phosphate content 82%-97%. The maximum absorption time is 24 hours of contact time. This is because the ammonia content can be reduced by 46% - 82% and the phosphate content can be reduced by 33% - 56%.